PENGARUH LIKUIDITAS, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Savsavubun, Sari Indah Setio Maria; Hwihanus (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the effect of liquidity, leverage, and dividend policy on firm value with profitability as a mediating variable. Liquidity is measured using the current ratio (CR), leverage using the debt to equity ratio (DER), dividend policy using the dividend payout ratio (DPR), profitability using return on assets (ROA), and firm value is measured through price to book value (PBV). The research sample consists of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during a certain period, selected using the purposive sampling method. The data analysis technique used is path analysis with mediation testing using the Sobel test method. The results of the study indicate that liquidity and leverage have a negative effect on firm value, while dividend policy has a positive effect. Profitability is proven to be a significant mediating variable in the relationship between liquidity and leverage on firm value, but does not mediate the effect of dividend policy. This finding indicates that management needs to pay attention to liquidity management policies and capital structure to increase profitability, which ultimately has an impact on increasing firm value. In addition, a consistent and optimal dividend policy can create a positive perception from investors, thereby increasing the attractiveness of the company's shares. This study provides theoretical contributions in understanding the role of profitability as a mediating variable in the relationship between financial variables and practical implications for corporate management in developing strategies to increase corporate value. This study also recommends further research by considering other industrial sectors and longer research periods.